Impaired small fiber conduction in patients with Fabry disease: a neurophysiological case–control study - Üçeyler, Nurcan (BioMed Central, 2013)
BACKGROUND: Fabry disease is an inborn lysosomal storage disorder which is associated with small fiber neuropathy. We set out to investigate small fiber conduction in Fabry patients using pain-related evoked potentials (PREP). METHODS: In this case–control study we prospectively studied 76 consecutive Fabry patients for electrical small fiber conduction in correlation with small fiber function and morphology. Data were compared with healthy controls using non-parametric statistical tests. All patients underwent neurological examination and were investigated with pain and depression questionnaires. Small fiber function (quantitative sensory testing, QST), morphology (skin punch biopsy), and electrical conduction (PREP) were assessed and correlated. Patients were stratified for gender and disease severity as reflected by renal function. RESULTS: All Fabry patients (31 men, 45 women) had small fiber neuropathy. Men with Fabry disease showed impaired cold (p < 0.01) and warm perception (p < 0.05), while women did not differ from controls. Intraepidermal nerve fiber density (IENFD) was reduced at the lower leg (p < 0.001) and the back (p < 0.05) mainly of men with impaired renal function. When investigating A-delta fiber conduction with PREP, men but not women with Fabry disease had lower amplitudes upon stimulation at face (p < 0.01), hands (p < 0.05), and feet (p < 0.01) compared to controls. PREP amplitudes further decreased with advance in disease severity. PREP amplitudes and warm (p < 0.05) and cold detection thresholds (p < 0.01) at the feet correlated positively in male patients. CONCLUSION: Small fiber conduction is impaired in men with Fabry disease and worsens with advanced disease severity. PREP are well-suited to measure A-delta fiber conduction.